Knowledge Attitude and Practice Regarding Behaviour Counselling Techniques for Tobacco Cessation Among Interns of a Private Dental Institution - P.S, KARTHIKESON.; SAKTHI, SRI; KUMAR, KIRAN (The journal of contemporary issues in business and government, 2021)
Physicians and dental practitioners play an important role in smoking cessation since many patients attempt to quit smoking by frequent visits and following physician’s advice . Although many dentists express a positive attitude to educate smoking cessation among patients, few relatively assist smokers to quit. It is important for the dentists to know about smoking cessation and its significance in changing behaviour of smokers.The aim of this study is to find out the knowledge, attitude and practice among interns regarding tobacco cessation and counselling techniques.This cross sectional study is done in form of an online survey comprising 15 questions regarding knowledge, attitude and practice regarding tobacco succession. The survey was distributed to 110 interns of private dental college only after their consent. Responses were recorded in Google forms with inclusion of one week scheduling. 90% of response rate was observed.Knowledge (63%), attitude (70%) ,practise (30%) among interns were observed. Overall knowledge and attitude among interns regarding tobacco cessation was found to be fair. Within the limitations of current study, knowledge attitude and practice regarding tobacco cessation was fair overall among interns of private dental college